Зловживання військовою службовою особою владою та службовим становищем в умовах особливого періоду та воєнного стану - Бурдін, М. Ю.; Burdin, M. Yu.; Юшкевич, О. Г.; Yushkevych, O. H.; Mykhailo Burdin; Юшкевич Олена Геннадіївна (Вісник Кримінологічної асоціації України. – 2024. – № 2 (32). – С. 622-636, 2024)
Проаналізовано особливості притягнення до адміністративної відповідальності військової службової особи за зловживання владою та службовим становищем в умовах особливого періоду та воєнного стану. Встановлено, що зловживання військовими службовцями владою та своїм службовим становищем часто є складним для виявлення та доведення через особливості військових структур і специфіку діяльності в умовах воєнного стану. Наведено два підходи до розуміння зловживання правом як загального правового явища по відношенню до зловживання владою та службовим становищем. Розглянуто судову практику у справах про зловживання владою та службовим становищем.

The features of holding military officers administratively liable for abuse of power and official position during a special period and under martial law have been analyzed. A classification of military administrative offenses has been provided, contributing to a more effective approach to regulating the administrative liability of military personnel. The composition of the administrative offense "abuse of power or official position by a military officer" has been defined. It has been established that the legal status of military personnel, particularly their administrative and legal status, significantly differs from the general legal status of a citizen. This difference manifests in the possibility, and more often the inevitable necessity, of transforming their general responsibility into specific, special responsibility. Historically, to ensure the country's defense capabilities and maintain order in the military sphere, the jurisdiction of civilian authorities has been limited, applying to military personnel only for certain administrative offenses. The understanding of concepts such as "abuse of power", "abuse of authority" and "abuse of rights" has been examined, and the interrelationship between them has been identified. Judicial practice concerning the abuse of power or official position by military personnel has been analyzed, identifying forms of such abuse – illegal use of subordinate military personnel for tasks not related to military service during martial law, and misuse of military property. It has been determined that abuse of power and official position by military personnel is often difficult to detect and prove due to the peculiarities of military structures and the specific nature of activities under martial law.

Проанализированы особенности привлечения к административной ответственности военного должностного лица за злоупотребление властью и служебным положением в условиях особого периода и военного положения. Установлено, что злоупотребление военными служащими властью и своим служебным положением часто сложно для выявления и доказывания из-за особенностей военных структур и специфики деятельности в условиях военного положения. Приведены два подхода к пониманию злоупотребления правом как общего правового явления по отношению к злоупотреблению властью и служебным положением. Рассмотрена судебная практика по делам о злоупотреблении властью и служебным положением.
Abuse of power and official position by a military official in the conditions of a special period and martial law
Keywords: зловживання правом; зловживання повноваженнями; військова службова особа; адміністративна відповідальність; завдання шкоди; воєнний стан; abuse of law; abuse of authority; military official; administrative responsibility; causing harm; martial law; злоупотребление правом; злоупотребление полномочиями; военное должностное лицо; административная ответственность; причинение вреда; военное положение